A MIV-150/Zinc Acetate Gel Inhibits SHIV-RT Infection in Macaque Vaginal Explants - Barnable, Patrick (Public Library of Science, 2014)
To extend our observations that single or repeated application of a gel containing the NNRTI MIV-150 (M) and zinc acetate dihydrate (ZA) in carrageenan (CG) (MZC) inhibits vaginal transmission of simian/human immunodeficiency virus (SHIV)-RT in macaques, we evaluated safety and anti-SHIV-RT activity of MZC and related gel formulations ex vivo in macaque mucosal explants. In addition, safety was further evaluated in human ectocervical explants. The gels did not induce mucosal toxicity. A single ex vivo exposure to diluted MZC (1∶30, 1∶100) and MC (1∶30, the only dilution tested), but not to ZC gel, up to 4 days prior to viral challenge, significantly inhibited SHIV-RT infection in macaque vaginal mucosa. MZC's activity was not affected by seminal plasma. The antiviral activity of unformulated MIV-150 was not enhanced in the presence of ZA, suggesting that the antiviral activity of MZC was mediated predominantly by MIV-150. In vivo administration of MZC and CG significantly inhibited ex vivo SHIV-RT infection (51–62% inhibition relative to baselines) of vaginal (but not cervical) mucosa collected 24 h post last gel exposure, indicating barrier effect of CG. Although the inhibitory effect of MZC (65–74%) did not significantly differ from CG (32–45%), it was within the range of protection (∼75%) against vaginal SHIV-RT challenge 24 h after gel dosing. Overall, the data suggest that evaluation of candidate microbicides in macaque explants can inform macaque efficacy and clinical studies design. The data support advancing MZC gel for clinical evaluation.